Increased functional connectivity in intrinsic neural networks in individuals with aniridia - Pierce, Jordan E.; Krafft, Cynthia E.; Rodrigue, Amanda L.; Bobilev, Anastasia M.; Lauderdale, James D.; McDowell, Jennifer E. (Frontiers in Human Neuroscience, 2014)
Mutations affecting the PAX6 gene result in aniridia, a condition characterized by the lack of an iris and other panocular defects. Among humans with aniridia, structural abnormalities also have been reported within the brain. The current study examined the functional implications of these deficits through “resting state” or task-free functional magnetic resonance imaging in 12 individuals with aniridia and 12 healthy age- and gender-matched controls. Using independent components analysis and dual regression, individual patterns of functional connectivity associated with three intrinsic connectivity networks (executive control, primary visual, and default mode) were compared across groups. In all three analyses, the aniridia group exhibited regions of greater connectivity correlated with the network, while the controls did not show any such regions. These differences suggest that individuals with aniridia recruit additional neural regions to supplement function in critical intrinsic networks, possibly due to inherent structural or sensory abnormalities related to the disorder.